2007
DOI: 10.1116/1.2779048
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of ultrahigh aspect ratio freestanding gratings on silicon-on-insulator wafers

Abstract: Articles you may be interested inFabrication of nanoscale, high throughput, high aspect ratio freestanding gratings J. Vac. Sci. Technol. B 30, 06FF03 (2012); 10.1116/1.4755815 High-efficiency, large-bandwidth silicon-on-insulator grating coupler based on a fully-etched photonic crystal structure Appl. Phys. Lett. 96, 051126 (2010);The authors report a silicon-on-insulator ͑SOI͒ process for the fabrication of ultrahigh aspect ratio freestanding gratings for high efficiency x-ray and extreme ultraviolet spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 18 publications
1
51
0
1
Order By: Relevance
“…It is commonly observed that high-aspect-ratio structures cluster at their tips, due to van der Waals or electrostatic charges on the newly formed surfaces, [31] facilitated by capillary forces present during drying after liquid immersion. [32] If the attractive forces between wires are greater than the force required to bend the wires, sheaflike structures result as the wires stick together, as shown in Figure 6a. The capillary force present during drying results primarily from surface tension at the solid/liquid interface as the liquid evaporates.…”
Section: Control Of Size Distributions Aspect Ratios Densities Andmentioning
confidence: 99%
“…It is commonly observed that high-aspect-ratio structures cluster at their tips, due to van der Waals or electrostatic charges on the newly formed surfaces, [31] facilitated by capillary forces present during drying after liquid immersion. [32] If the attractive forces between wires are greater than the force required to bend the wires, sheaflike structures result as the wires stick together, as shown in Figure 6a. The capillary force present during drying results primarily from surface tension at the solid/liquid interface as the liquid evaporates.…”
Section: Control Of Size Distributions Aspect Ratios Densities Andmentioning
confidence: 99%
“…Fabrication of such membranes has been successful in metallic systems, 6,7 but has proven challenging in semiconductors like silicon. Freestanding silicon membranes have applications in electronic and photonic materials, [8][9][10][11] micromechanical devices, [12][13][14][15][16] x-ray optics, [17][18][19] macromolecular filters, 20 lithographic templates, 17,19 as sensors, 21,22 and as low-absorption supports in transmission electron microscopy. All of these applications benefit from flat crystalline structures with low lateral inhomogeneity.…”
mentioning
confidence: 99%
“…15,20 The process improvements we have employed since these measurements were taken have greatly reduced the frequency of any SEM-detectable defects. Thus we believe that the diffraction efficiencies can still be improved.…”
Section: Extreme Ultraviolet and Soft X-ray Diffraction Efficienciesmentioning
confidence: 99%
“…We developed a fabrication process that uses a <110> silicon-on-insulator (SOI) wafer as a starting point with a device layer thickness equal to the desired grating thickness d. 20 The four main process steps are front side patterning, backside patterning and etching, front side etching, and supercritical drying. The resulting front side patterns consist of a chrome mask that defines a coarse support mesh, and a silicon nitride mask for the CAT grating bars, defined by scanning-beam interference lithography (SBIL).…”
Section: Fabrication Of Cat Grating Prototypesmentioning
confidence: 99%